2005
DOI: 10.1590/s0100-879x2005000500002
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory enlargement of human coronary arteries identified by magnetic resonance imaging

Abstract: The aim of the present study was to evaluate the role of magnetic resonance imaging (MRI) for the non-invasive detection of coronary abnormalities and specifically the remodeling process in patients with coronary artery disease (CAD). MRI was performed in 10 control healthy subjects and 26 patients with angiographically proven CAD of the right coronary (RCA) or left anterior descending (LAD) artery; 23 patients were within two months of acute coronary syndromes, and 3 had stable angina with a positive test for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, a thickening of vascular walls was observed but the internal diameter of vessels was preserved in HFD-fed LDLR -/-mice while external diameter was increased. Several studies have reported similar results regarding the enlargement of vessel in plaque sites using magnetic resonance or intravascular ultrasound imaging [34,35]. This enlargement is described as a compensatory response for intimal hyperplasia formation that may lead to vascular expansive remodeling [36].…”
Section: Effect Of Hfd On Aortic Arch Morphologymentioning
confidence: 81%
“…Interestingly, a thickening of vascular walls was observed but the internal diameter of vessels was preserved in HFD-fed LDLR -/-mice while external diameter was increased. Several studies have reported similar results regarding the enlargement of vessel in plaque sites using magnetic resonance or intravascular ultrasound imaging [34,35]. This enlargement is described as a compensatory response for intimal hyperplasia formation that may lead to vascular expansive remodeling [36].…”
Section: Effect Of Hfd On Aortic Arch Morphologymentioning
confidence: 81%
“…[100][101][102][103] We have already detected by magnetic resonance imaging coronary vessel wall modifications, e.g., increases in wall thickness, vessel wall area, and total vessel area in patients with coronary artery disease compared to normal controls. 104 Interestingly, the luminal area was preserved in these patients in spite of the presence of large plaque volumes (Figure 2). Thus, magnetic resonance imaging to determine the luminal area/total vessel area ratio is a noninvasive method for detecting coronary vessel wall modifications including remodeling and for clearly differentiating patients with coronary artery disease from healthy subjects despite a similar lumen (Figures 3a, 3b).…”
Section: High-resolution Mri For Plaque Characterizationmentioning
confidence: 90%
“…Magnetic resonance of coronary arteries. Positive remodeling of coronary arteries indicated by increased wall thickness, wall area, and total vessel area with preservation of luminal area104 …”
mentioning
confidence: 99%
See 1 more Smart Citation